ESTIMASI BIOMASSA HUTAN RAKYAT FOREST MANAJEMEN UNIT (FMU) LAWU MANUNGGAL KECAMATAN PANEKAN KABUPATEN MAGETAN (Kasus Desa Tapak Kecamatan Panekan Kabupaten Magetan) - Lukito, Martin; Rohmatiah, Ahadiati (JURNAL AGRI-TEK, 2018)
Efforts to anticipate the impacts of climate change, already or maybe will happen is by mitigation by multiplying the forest stands. The objective of this research is to know the content of forest biomass of the People's Forest Management Unit (FMU) Lawu Manunggal village Tapak District Panekan. Research Methods. Inventory of stands with the manufacture of plots of 0.05 Ha wide circle. Biomass estimation by destructive sampling method. Typical forest area Tapak Village 244 Ha, consists of 4 types of stands like mindi, Mahogany, Teak and Sengon. Potential of Biomass per Ha Mindi type 90.53 ton / Ha, Mahogany: 102,210 Ton / Ha, Teak 69,849 ton / Ha Sengon 33,480 ton / Ha. Stem organs have a contribution of 59.30%, branch: 10.94%, leaves 9.63% and roots 20.13% of total standing biomass. Total Village Biomass Tapak of 3,227.74 Ton consists of Mindi Type 905.34 Ton, Mahoni 1,289.11 tons, Teak 689.49 Ton and Sengon of 334.80 tons. Keywords: Mitigation, Biomass, Forest People